Asset Recovery as a Fundamental Principal in Law Enforcement of Corruption by Corporations - Nani Mulyati; Aria Zurnetti (Andalas International Journal of Socio-Humanities, 2022)
Corruption is one of the most widespread and chronic crimes in Indonesia. Therefore, handling corruption is a very important priority for law enforcement. Perpetrators of corruption are not only individuals but also corporations. The crime is done for the benefit of the corporation itself. Today corruption committed by corporations have started to be a concern of law enforcement officials even though the implementation is not yet optimal. This paper discusses the assets recovery as a fundamental principal in criminal punishment against a corrupt corporation. This research is using a dogmatic legal method by analyzing legal materials. From the research conducted it can be concluded that law enforcement of criminal acts of corruption carried out by corporations should be prioritized in the asset recovery principal and not only aiming to punish criminal offenders. So it is recommended to law enforcement officials to use asset recovery approach in handling corruption cases committed by corporations, including in pairing the indictment with money laundering regime.